Developing an Educational Package through Handbook of How to Express Breast Milk for Working Mother at Sumberejo Banyuputih Village in Situbondo - Ningsih, Dewi Andariya; Rohmah, Miftakhur (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The phenomenon showed that half of the mothers felt lazy to breastfeed their baby. It happened not only in the developed country but also in the developing country such as Indonesia, especially in big cities. The aim of this research was to produce an educational product in the form of a handbook of how to express breast milk for working mother in order to improve their knowledge. The sample of this research was 33 pregnant mothers of 2nd and 3rd trimester. The design of this research was a Research and Development (R&D). The result of Wilcoxon test showed positive ranks which indicated all of the respondents’ knowledge improved after the intervention. The implication of this research was to ease pregnant mothers in studying expressed breast milk handbook because the handbook can be used every time and everywhere by anyone.